Formulation and Evaluation of Polymer Effect on In-Vitro Kinetics of Sustained Release Matrix Tablets of Carvedilol Using Model Dependent Methods (International Journal of Pharmaceutical and Life Sciences, 2013)
The present study was designed to evaluate the polymeric effect of METHOCEL K15MCR on the sustained release drug product of Carvedilol. Carvedilol matrix tablets were formulated by direct compression method using METHOCEL K15MCR polymer in various percentages. Physical parameters were tested and the dissolution procedure was performed by using USP (II) paddle method for eight hours to examine the release kinetics. In the study, METHOCEL K15MCR polymer was found to cause the strong retardation of the drug release. The release mechanism was explored and explained with zero order, first order, Higuchi and Korsmeyer-Peppas equations. In the context, it can be suggested with a satisfactory result that this sustained release Carvedilol tablets can be marketed to treat patient ensuring proper healthcare. DOI: http://dx.doi.org/10.3329/ijpls.v2i2.15452 International Journal of Pharmaceutical and Life Sciences Vol.2(2) 2013: 70-79